Prevalence of macrolide- and fluoroquinolone-resistant Mycoplasma genitalium strains in clinical specimens from men who have sex with men of two sexually transmitted infection practices in Berlin, Germany. (September 2019) - Dumke, Roger; Ziegler, Thomas; Abbasi-Boroudjeni, Naghmeh; Rust, Marcos; Glaunsinger, Tobias
Highlights: 154 Mycoplasma genitalium -positive samples from outpatients were tested using sequencing. 79.9% of strains showed mutations associated with macrolide resistance. The rate of quinolone resistance was 13.0%. Eighteen strains (11.7%) were potentially macrolide- and quinolone-resistant. High resistance rates require more attention among physicians treating MSM. Abstract: Objectives: The cell-wall-less Mollicutes species Mycoplasma genitalium is a sexually transmitted micro-organism that causes different male and female genital tract infections. In recent years, resistance of the pathogen to macrolides and fluoroquinolones has been increasingly reported worldwide and is more frequent in risk groups. Methods: To determine the rates of antimicrobial resistance, M. genitalium strains in 195 specimens from 154 outpatients (154 first and 41 follow-up samples) treated in two specialised practices between September 2017 and December 2018 in Berlin, Germany, were analysed. Results: The included patients were predominantly men who have sex with men (MSM) (91.6%) and were HIV-positive in many cases (49.4%). Only 27.3% of M. genitalium -positive patients reported symptoms. Among the first samples (mainly rectal swabs) (57.8%), mutations associated with macrolide (23S rRNA) and quinolone ( parC gene) resistance were detected in 79.9% and 13.0% of strains, respectively. Resistance to both classes of antibiotics was found in 11.7% of specimens. Changes of A → G at position 2072 of 23S rRNA and of serine at position 83 of ParC were the most frequent alterations. Conclusion: Although azithromycin is recommended as a first-line antibiotic to treat infections with M. genitalium in MSM, according to these data its use must be highly limited in Berlin. Besides the need for resistance studies regarding strains circulating in other locations and among different patient groups in Germany, the results emphasise the importance of intensified antibiotic resistance testing of M. genitalium to avoid a further increase in treatment failures in infections with this emerging human pathogen.